How does climate exacerbate root causes of conflict in Nigeria? An econometric analysis - Belli, Anna; Villa, Victor; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet assesses how climate exacerbates root causes of conflict in Nigeria, using a two-stage econometric approach. The findings show how increased rainfall increases the nutrition security of Nigerian households and that the combined effect of extreme temperature and nutrition insecurity increases the intensity of conflicts.